Tanggapan Anies Baswedan Mengenai Pengentasan Kemiskinan di Utasan Platform X - Annisa Dhea Nurbaity (Program Studi Magister Linguistik Terapan UNJ, 2025)
Poverty is a structural issue that continues to be a persistent discourse in Indonesia. Social media, especially the X platform (formerly Twitter), has become a new space for political figures to convey their narratives, including poverty-related issues. This article analyzes the discourse strategy of Anies Baswedan, former Governor of Jakarta and 2024 presidential candidate, in a thread dated May 3, 2025, which addresses the causes and solutions of poverty. Using a qualitative case study approach, the research examines 14 tweets through Halliday’s Systemic Functional Linguistics (2014) and Fairclough’s Critical Discourse Analysis framework (2003). The findings indicate that Anies frames poverty as a structural problem that requires empathetic and systemic solutions. His discourse strategy emphasizes inclusivity, empathy, and public appreciation. Anies positions himself as someone who understands social inequality and proposes practical solutions based on his leadership experience in Jakarta. Thus, the discourse he constructs is not only informative but also socially and politically persuasive and the provided solution may serve as a basis for formulating faires social policies.